Utilization of Milkfish Bones and Heads from CV. Maharani Dwi Bayu Kalanganyar Sidoarjo for Making Spicy Fish Sauce: Pemanfaatan Tulang dan Kepala Bandeng dari CV. Maharani Dwi Bayu Kalanganyar Sidoarjo untuk Pembuatan Kecap Ikan Pedas - Sri Winarti; Titi Susilowati (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Kalanganyar is a village whose 2/3 area consists of ponds and producers of milkfish, tiger prawns, shrimp paste, processed milkfish and crackers. Most of the milkfish from Kalanganyar are sold fresh, but some are processed into various processed products, including smoked milkfish, shredded milkfish, crackers, soft spiny milkfish and crispy milkfish. One of the producers of crispy milkfish is CV. Maharani Dwi Bayu. Milkfish that is processed into crispy milkfish will leave behind waste in the form of heads, tails and milkfish bones/spines. So far, this waste has not been utilized optimally. To overcome this problem, the heads and bones of milkfish are used as raw materials for making spicy fish sauce. The resulting soy sauce can be used as a complement to smoked milkfish or presto milkfish as a substitute for chili sauce. Training has been carried out on processing fish sauce at CV. MAHARANI DWI BAYU, Jalan Raya Kalanganyar Wetan, Sedati District, Sidoarjo Regency. Apart from holding training on processing fish sauce from milkfish bones and heads, supporting equipment for soy sauce processing was also handed over, namely pressure cookers, vacuum filters, steamers and hot guns. The people of Kalanganyar are very happy and enthusiastic about taking part in training to gain new knowledge and new innovative products.